2022
DOI: 10.1021/acs.macromol.2c00016
|View full text |Cite
|
Sign up to set email alerts
|

Extrudable Vitrimeric Rubbers Enabled via Heterogeneous Network Design

Abstract: The state-of-the-art reprocessing of vitrimers still struggles in crude hot-compression processes. The highly cross-linked nature and glass-like viscoelastic behavior of vitrimers critically restrict the network chain mobility, which limits the application of continuous processing techniques during reprocessing. Herein, a multiphase design strategy is outlined through incorporating highly cross-linked vitrimeric powders into a polymer matrix, followed by cross-linking with dynamic covalent bonds (DCBs) contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…46 As a result, rubber vitrimers often show significantly longer relaxation times than epoxy vitrimers. To obtain rubber vitrimers with favorable dynamic properties, several DCBs with high dynamic activity (such as the boronic ester bond 47,48 and disulfide bond [49][50][51] ) have been proposed for rubber networks. Wu and Huang et al 52 constructed a rubber vitrimer with ester bonds and disulfide bonds, which showed rapid relaxation ability and improved mechanical properties, by a self-strengthening strategy after network rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…46 As a result, rubber vitrimers often show significantly longer relaxation times than epoxy vitrimers. To obtain rubber vitrimers with favorable dynamic properties, several DCBs with high dynamic activity (such as the boronic ester bond 47,48 and disulfide bond [49][50][51] ) have been proposed for rubber networks. Wu and Huang et al 52 constructed a rubber vitrimer with ester bonds and disulfide bonds, which showed rapid relaxation ability and improved mechanical properties, by a self-strengthening strategy after network rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the cross-linking network of EUG-OH-BDBA was confirmed by the swelling ratio in different solvents (Figure S4). After being immersed for 7 days, EUG-OH-BDDA-1 hardly swelled in water and ethanol, but the swelling rate in tetrahydrofuran and xylene is 653 and 632%, respectively, which is similar to vulcanized rubber …”
Section: Resultsmentioning
confidence: 83%
“…After being cured by BDBA, the stretching vibration peak of −OH at 3417 cm −1 decreased significantly, and the bending vibration peak of −OH at 1548 cm −1 disappeared, while a new absorption peak attributed to B−O stretching vibration appeared at 1263 cm −1 . 48 These results indicate that the −OH of EUG-OH reacts with BDBA to from borate ester bonds. The curing behavior was monitored by moving the die rheometer, and the increase in torque (elastic modulus) demonstrates the formation of a cross-linking network (Figure 2b).…”
Section: Preparation and Characterization Of Eug-oh-bdbamentioning
confidence: 86%
See 1 more Smart Citation
“…The polar ionic groups tend to aggregate into microphase-separated ionic-rich domains in the nonpolar elastomer matrix, acting as physical cross-links and reinforcing points. The ionomeric elastomers can show shape memory behavior and self-healing ability due to the dynamic nature of ionic interactions. In the past decades, dynamic covalent polymer networks have provided another avenue for recycling elastomers at end of life due to their thermoplastic-like properties. However, the researchers were still struggling in crude hot-compression processes for the reprocessing of dynamic covalent polymers. Recently, TPEs have become the most rapidly growing elastomers as substitutes for nonrecyclable cross-linked rubbers due to the requirement for resource-saving and sustainable development. However, most commercially available TPEs are derived from petroleum-derived products; thus, it is highly desirable to find a nonfood, renewable feedstock alternative to petroleum derivatives.…”
Section: Introductionmentioning
confidence: 99%